A word-count approach to analyze linguistic patterns in the reflective writings of medical students. Issue 1 (1st January 2016) - Lin, Chi-Wei; Lin, Meei-Ju; Wen, Chin-Chen; Chu, Shao-Yin
Abstract : Background: Teaching reflection and administering reflective writing assignments to students are widely practiced and discussed in medical education and health professional education. However, little is known about how medical students use language to construct their narratives. Exploring students' linguistic patterns in their reflective writings can facilitate understanding the scope and facets of their reflections and their representational or communication approaches to share their experiences. Moreover, research findings regarding gender differences in language use are inconsistent. Therefore, we attempted to examine how females and males differ in their use of words in reflective writing within our research circumstance to detect the unique and gender-specific approaches to learning and their applications. Methods: We analyzed the linguistic profiles of psychological process categories in the reflective writings of medical students and examined the difference in word usage between male and female medical students. During the first year of a clinical rotation, 60 fifth-year medical students wrote reflective narratives regarding pediatric patients and the psychosocial challenges faced by the patients and their family members. The narratives were analyzed using the Chinese version of Linguistic Inquiry and Word Count (CLIWC), a text analysis software program. Multivariate procedures were applied for statistical analysis. Results: Cognitive words were most pervasive, averaging 22.16%, whereas perceptual words (2.86%) were least pervasive. Female students used more words related to positive emotions and sadness than did male students. The male students exceeded the female students only in the space category. The major limitation of this study is that CLIWC cannot directly acquire contextual text meanings; therefore, depending on the research topic, further qualitative study of the given texts might be necessary. Conclusions: To enhance students' empathy toward the psychosocial issues faced by patients and their family members, students should be encouraged to explore the domain of psychological processes by identifying and expressing their affective and perceptual experiences. Researchers in future studies should use outcome measures such as self-awareness or empathy to determine the overall effectiveness of reflective writing and how changes in linguistic patterns affect such outcomes.